CLANDESTINE LABORATORY: ANALISIS FAKTOR PENDORONG BERKEMBANGNYA LABORATORIUM GELAP NARKOBA DI INDONESIA DALAM KONTEKS TRANSNATIONAL ORGANIZED CRIMES (TNOCs) - Leebarty Taskarina (Jurnal Kriminologi Indonesia, 2010)
This research discusses about phenomenon of clandestine laboratory in Indonesia. This study starts from the background problems which found that clandestine laboratory producing ecstasies and methamphetamine in some regions of Indonesia. This issue then makes author interested to discuss deeper about the production of illegal drugs at clandestine laboratory that revealed in Indonesia. This research tries to describe about the pattern of clandestine laboratory in Indonesia and the factors that will encourage the clandestine laboratory’s development in Indonesia. This study also aims to identify the clandestine laboratory activity as one form of transnational organized crime’s spread after globalization. This is a descriptive qualitative research, where the data was collected by using case files, and structured interviews. This research is conducted by analyzing files of clandestine laboratory cases that occurred in Indonesia in last five years. The results of this research answers questions about what factors encourage the development of clandestine laboratory in Indonesia. These factors are, the easiness to obtain chemicals, chemical devices, and also cooperation with foreign syndicates, which often employ drugs designer to produce illegal drugs. This research concludes that the clandestine laboratory can be developed in Indonesia because the perpetrator’s accesses to get basic chemicals drugs maker (precursor) are very easy, the use of controlled legal chemicals are leak frequently and it was used to make drugs, free sales of supporting chemical devices, and involvement of foreign drugs designer to teach how to make drugs.The results of this study tell that clandestine laboratory will continue to increase if the minimization of the perpetrator access to produce the drugs done as early as possible. Certainly, the phenomenon of clandestine laboratory can be minimized, at least to suppress the circulation of drugs in Indonesia itself.